Data mining project final report. NHL playoff prediction - Heal, B.; Kimball, M.; Fung, R.; Alenazi, A. (NHL Playoff Prediction, April 2016, 2016)
What goes into winning the Stanley Cup in the National Hockey League (NHL)? The obvious things include deep offence, a smart defence and a goaltender who is able to make all the important saves. In this project we looked at quantifiable measures of some of those attributes and used algorithms to determine which team has the statistical advantage for the 2016 Stanley Cup Playoffs. We found an existing dataset and expanded on it using our own interpretation of the feature vectors. After creation of the combined dataset, we trained and tested several classifiers including an artificial neural network in single game prediction, and applied this to playoff series prediction.